Traditional games as playful methodological strategies for the teaching-learning process of mathematics - Marcillo-Zambrano, María Mercedes; Ureta-Velásquez, Virginia Elizabeth (International research journal of management, IT and social sciences, 2025)
This research analyzed how traditional games can be used as playful methodological strategies in mathematics learning to enhance numerical thinking in elementary school students at the "10 de Julio" Educational Unit in Chapuli, Manabí, Ecuador. The results of the research, obtained through observation, are presented as a way to project the level of complexity students encounter in this subject and the need to analyze how traditional games represent a valuable educational resource. The challenges students face in learning mathematics include various difficulties that lead to errors in basic operations, hindering their progress in the development of numerical thinking. A classification of topics on the potential of traditional games was carried out within the theoretical framework. The importance of numerical thinking for improving learning and applying it in daily life was also highlighted. The objective was to determine the level of complexity that students in Basic General Education experience in the teaching and learning process of Mathematics regarding the implementation of traditional games as playful methodological strategies in the institution under investigation. The study employed a mixed-methods approach, combining qualitative and quantitative methods, as well as inductive and heuristic analysis.